La teoría marxista y los dilemas de la acción colectiva. - Cruz Rodríguez, Edwin (Revista Pensamiento Americano, 2015)
Main problems faced by Marx theory aiming to explain Agency structure, subject problem and vanguard/ spontaneity dilemma is addressed in this paper. Although Marxism has ceased to be a paradigm to explain the collective action, problems and questions arose from this three dilemmas fully, answers are still demanded. Therefore, its study might be a way to suggest an hypothesis or at least to understand knowledge limitations in this research field.